Plutonium retention in the isosaccharinate – cement system. (March 2021) - Tasi, A.; Gaona, X.; Rabung, Th.; Fellhauer, D.; Rothe, J.; Dardenne, K.; Lützenkirchen, J.; Grivé, M.; Colàs, E.; Bruno, J.; Källstrom, K.; Altmaier, M.; et al.
Abstract: Uptake of plutonium by Portland cement in degradation stage II was investigated in the presence of α-D-isosaccharinic acid (ISA) under reducing conditions set by hydroquinone, Sn(II) or Na2 S2 O4 . Sorption experiments were performed at log [Pu]in  = −6 to −9, log [ISA]tot  = −6 to −2 and with solid to liquid ratios (S:L) of 0.1–50 g⋅dm −3 . ISA sorbs strongly on cement, causing a significant decrease in the ζ potentials of cement particles above log [ISA]tot  ≥ −3.5 at S:L ≤ 4 g⋅dm −3 . Sorption of Pu significantly decreases above log [ISA]tot  ≥ −4.5 due to the competing formation of aqueous Ca(II)–Pu(IV)–ISA complexes. The increased retention of Pu observed above ∼25% of surface coverage by ISA is attributed to the co-adsorption of Pu(IV) with ISA. The impact of the order of addition of individual components on Pu sorption kinetics can be on the scale of several years. Graphical abstract: Image 1 Highlights: Pu(III/IV) sorb strongly onto cement under alkaline, reducing conditions. Isosaccharinic acid (ISA) has a substantial impact on the retention of Pu(IV). Above ∼25% of surface coverage by ISA, Pu(IV) co-adsorbs with ISA onto cement. Kinetics of the sorption process depends on the order of addition of the components. Based on previous thermodynamic models, a simplified sorption model is derived.